2018
DOI: 10.1111/ejh.13157
|View full text |Cite
|
Sign up to set email alerts
|

Immune surveillance by autoreactive CD4‐positive helper T cells is a common phenomenon in patients with acute myeloid leukemia

Abstract: We demonstrated that the presence of AML-directed autoreactive T cells is a common phenomenon which appears to be part of the general T-cell repertoire also in healthy individuals. This autoreactive AML-directed T-cell response may directly contribute to anti-AML immune surveillance especially in the situation of minimal residual disease, but furthermore the immune-modulatory effect on the AML phenotype may pave the way for other immunological interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Such reasons have aroused great interest in the scientific community for the study of immunomodulation, with the aim of preventing diseases, rather than treating them in their already advanced state. In addition, numerous analyses in cancer survivor patients have identified the activation of certain immunological patterns related to the phenomenon of immunosurveillance, which would activate certain adaptive mechanisms to develop antibodies that inhibit the “stop” signals that cancers generate to prevent T cells from acting against them [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such reasons have aroused great interest in the scientific community for the study of immunomodulation, with the aim of preventing diseases, rather than treating them in their already advanced state. In addition, numerous analyses in cancer survivor patients have identified the activation of certain immunological patterns related to the phenomenon of immunosurveillance, which would activate certain adaptive mechanisms to develop antibodies that inhibit the “stop” signals that cancers generate to prevent T cells from acting against them [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immune surveillance is an important prerequisite for distant invasion and metastasis of tumour cells [8]. It is reported that various solid tumours are infiltrated with a large number of lymphocytes, which are positively correlated with the prognosis of patients [9]. Although tumour tissues are infiltrated by a large number of immune cells, it is still difficult to prevent the invasion and metastasis of tumour cells, suggesting that tumour cells can escape surveillance and killing by immune cells [10,11].…”
Section: Introductionmentioning
confidence: 99%